ANALISIS KEMISKINAN BERDASARKAN KARAKTERISTIK RUMAH TANGGA, FAKTOR KOMUNITAS DAN KARAKTERISTIK WILAYAH DI KECAMATAN GUNUNGPATI SEMARANG - Bhekti Sulistyo; Hadi Sasana (Diponegoro Journal of Economics, 2012)
ABSTRACT The expected goal in this study was to analyze the relationship Household characteristics,community factors, the characteristics of poverty in Sub Gunungpati Semarang. The population in this study were all located Households in the District for 14.579 households Gunungpati. The research was conducted using a sample of 100 persons / respondents. The sampling technique used in this study Purposive sampling technique is based on community or population that can be found by chance in 16 villages in the district Gunungpati. The results suggest that the relationship variable of household characteristics, community factors or characteristics of the region has influence in poverty. While relations simultaneously or jointly variable factors of household characteristics, community factors and characteristics of the region has influence on poverty. So the increase in household characteristics, community factors and characteristics of the region together can affect poverty in the District Gunungpati Semarang.